2024
DOI: 10.1109/trpms.2023.3324197
|View full text |Cite
|
Sign up to set email alerts
|

Scalable, Time-of-Flight and Depth-of-Interaction Detector Units for High-Resolution PET Systems

Vanessa Nadig,
Stefan Gundacker,
David Schug
et al.

Abstract: Resolving the depth of interaction (DOI) of a γ-photon in the scintillator is necessary to correct for parallax errors in organ-dedicated and large-scale time-of-flight positron emission tomography (TOF-PET) scanners or enable the precise recovery of Compton-scattered γ-photons. Doubling the number of readout channels and moving towards more complex detector designs are methods to encode DOI, often associated with high costs. We propose a DOI-capable TOF-PET detector unit concept confining light-sharing to two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Apart from reducing the power consumption [ 15 ], sophisticated shielding techniques may come into play to reduce the interference between components. First shielding attempts have been demonstrated using caskets [ 15 , 16 , 46 ]. Final 3D-integration could be facilitated by omitting the balun transformer as proposed in [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from reducing the power consumption [ 15 ], sophisticated shielding techniques may come into play to reduce the interference between components. First shielding attempts have been demonstrated using caskets [ 15 , 16 , 46 ]. Final 3D-integration could be facilitated by omitting the balun transformer as proposed in [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is expected to realize TOF resolutions close to the limits of photosensor and scintillator measured with the oscilloscope. A combination of this 16-channel HF readout with previous studies on TOF- and depth-of-interaction-capable detector units is as well planned [ 46 ]. Overall, it can be concluded that the presented electronic front end does not affect the timing performance of the back-end electronics used in single- and multi-channel experiments and is hence a promising readout approach to be connected to ultrafast, precise back-end electronics.…”
Section: Discussionmentioning
confidence: 99%